Human-Induced Pluripotent Stem Cell–Derived Cardiomyocyte Model for TNNT2 Δ160E-Induced Cardiomyopathy. (12th July 2022) - Kondo, Takumi; Higo, Shuichiro; Shiba, Mikio; Kohama, Yasuaki; Kameda, Satoshi; Tabata, Tomoka; Inoue, Hiroyuki; Okuno, Shota; Ogawa, Shou; Nakamura, Satoki; Takeda, Maki; Ito, Emiko; et al.
Abstract : Background: The Δ160E mutation in TNNT2, which encodes troponin T, is a rare pathogenic variant identified in patients with hypertrophic cardiomyopathy and is associated with poor prognosis. Thus, a convenient human model recapitulating the pathological phenotype caused by TNNT2 Δ160E is required for therapeutic development. Methods: We identified a heterozygous in-frame deletion mutation (c.478_480del, p.Δ160E) in TNNT2 in a patient with familial hypertrophic cardiomyopathy showing progressive left ventricular systolic dysfunction, leading to advanced heart failure. To investigate the pathological phenotype caused by Δ160E, we generated a set of isogenic induced pluripotent stem cells carrying the heterozygous Δ160E, homozygously corrected or homozygously introduced Δ160E using genome editing and differentiated them into cardiomyocytes (Hetero-Δ160E-, wild type-, and Homo-Δ160E-induced pluripotent stem cells [iPSC]-derived cardiomyocytes [iPSC-CMs]). Results: Hetero-Δ160E-iPSC-CMs exhibited prolonged calcium decay, relaxation impairment, and hypertrophy compared to wild type-iPSC-CMs. Notably, these phenotypes were further exacerbated in Homo-Δ160E-iPSC-CMs. Overexpression of R-GECO-fused Δ160E mutant troponin T prolonged decay time and time to peak of the myofilament-localized calcium transient in iPSC-CMs, indicating that sarcomeric calcium retention with Δ160E may affect intracellular calcium concentration. High-content imaging analysis detected remarkable nuclear translocation of NFATc1, especially in Homo-Δ160E-iPSC-CMs, indicating that the Δ160E mutation promotes hypertrophic signaling pathway in a dose-dependent manner. Increased phosphorylation of CaMKIIδ (calcium/calmodulin-dependent protein kinase IIδ) and phospholamban at Thr17 was observed in Homo- and Hetero-Δ160E-iPSC-CMs. Epigallocatechin-3-gallate, a calcium desensitizing compound, shortened prolonged calcium decay and relaxation duration in Δ160E-iPSC-CMs. Conclusions: Isogenic iPSC-CMs recapitulate the prolonged calcium decay, relaxation impairment, and subsequent calcium-regulated signaling pathways caused by the TNNT2 Δ160E mutation and can serve as a human model for therapeutic development to prevent hypertrophic cardiomyopathy pathology.